Effect of Remin Pro and Neutral Sodium Fluoride on Enamel Microhardness After Exposure to Acidic Drink - Azam Valian; Azadeh Raeisi-Sarkhooni; Elham Moravej-Salehi; Shila Emamieh (Islamic Dental Association of Iran, 2017)
Background and Aim: High consumption of carbonated diet soda is the most common etiologic factor for dental erosion. The purpose of this study was to evaluate the microhardness of the enamel surface eroded by cola after treatment with Remin Pro and neutral sodium fluoride. Materials and Methods: This in vitro experimental study was performed on 20 extracted premolars with no corrosion, abrasion, crack or hypocalcification. To properly evaluate the microhardness, the buccal surface of samples was polished with sandpaper and then the teeth were immersed in acidic drinks to achieve demineralization. Next, the microhardness was measured at three new points and the samples were randomly divid-ed into two groups for application of neutral sodium fluoride and Ramin Pro. Duration of treatment was in accord with the manufacturer's instructions and the microhardness of the samples was measured again. Results: Significant differences were found between the two groups after the treatment, and the fluoride group showed higher microhardness (P=0.04). Also, the microhardness value was significantly different at the three time points (P<0.001). Conclusion: Cola decreased the enamel microhardness while Remin Pro and neutral sodium fluoride increased the microhardness of enamel. Neutral sodium fluoride showed better remineralizing effect on enamel microhardness.